Primary scleral-fixated posterior chamber intraocular lenses in patients with congenital lens subluxation - Anjian Wang (BMC, 2021)
Abstract Objective We investigated the long-term visual outcomes and ocular complications of primary scleral-fixated posterior chamber intraocular lenses (SF-PC-IOLs) in patients with congenital lens subluxation. Methods We enrolled 53 patients (77 eyes) with congenital lens subluxation caused by ectopia lentis, Marfan syndrome, and Weill–Marchesani syndrome who underwent primary implantation of a SF-PC-IOL. All patients underwent a complete ophthalmic examination include visual acuity (VA), intraocular pressure (IOP), intraocular lenses (IOL) position, intraoperative complications and postoperative complications. Cox regression analysis and survival analysis were used to evaluate the risk factors for postoperative complications. Results Seventy seven eyes from 53 patients were included. Mean age at surgery was 23 ± 20 years (5 to 67 years), with a mean follow-up of 39 ± 27 months (12 to 130 months). The best-corrected VA improved from 0.84 ± 0.55 to 0.26 ± 0.43 logarithms of the minimum angle of resolution (p < 0.001). Best-corrected VA improved postoperatively in 73 eyes (94%). The main causes of reduced vision after surgery were retinal pathologies and amblyopia. Complications included transient intraocular haemorrhage (2 eyes, 2.6%), early vitreous incarceration (2 eyes, 2.6%), retinal detachment (6 eyes, 7.8%) and IOL dislocation (3 eyes, 3.9%). Cox regression showed that postoperative eye trauma was a risk factor for long-term postoperative complications. Conclusion SF-PC-IOLs provide good visual outcomes in patients with congenital lens subluxation. The SF-PC-IOLs showed good stability, except in patients suffering from postsurgical eye trauma.